Clinical, Molecular, Immunological Properties and Our Clinical Experiences in Patients Diagnosed with X-linked Agamaglobulinemia - Ezgi Balkarlı; Selime Özen Bölük; Ömer Akçal; İlke Taşkırdı; İdil Akay Haci; Nesrin Gülez; Ferah Genel (Galenos Publishing House, 2023)
Objective: As a primary immunodeficiency X-linked agammaglobulinemia (XLA) that develops due to Bruton tyrosine kinase signal transduction protein deficiency which progresses with antibody deficiency was firstly described by an American pediatrician Ogden Bruton. In our study, we have aimed to evaluate the demographic, clinical, immunological, genetic characteristics and follow-up findings of patients diagnosed with XLA in our tertiary care Pediatric Immunology Clinic. Method: Twelve patients diagnosed with XLA between 2003-2022 in our pediatric immunology clinic we're included in our study. The patient's age, sex, age at symptom onset and diagnosis, family history, laboratory findings at the time of diagnosis, complications observed during clinical follow-up and treatment modalities used were evaluated retrospectively. Results: The median age of the patients at diagnosis was 36 [interquartile range (IQR) 10.2-69.0] months. While the median age of the patients without a family history at the time of diagnosis was 66 (IQR 41.2-66.0) months which was found to be significantly higher compared to the patients with a family history [11.5 (IQR 2.5-30.0) months] (p=0.004). Recurrent respiratory tract infections were the most common indications for admission. Agammaglobulinemia was detected in all patients except two cases. A significant decrease in B cells was detected by flow cytometry in all patients. The diagnoses were confirmed by genetic analysis for nine patients. Bronchiectasis was observed in four, arthritis in three, and inflammatory bowel disease in one case. In one patient, metaplasia was detected in the cytologic examination of the biopsy specimen obtained during endoscopy performed for the diagnosis of inflammatory bowel disease. Conclusion: Early diagnosis, treatment and regular follow-up convey critical importance in terms of preventing complications in patients with XLA.